2009
DOI: 10.1073/pnas.0909333107
|View full text |Cite
|
Sign up to set email alerts
|

Axl is an essential epithelial-to-mesenchymal transition-induced regulator of breast cancer metastasis and patient survival

Abstract: Metastasis underlies the majority of cancer-related deaths. Thus, furthering our understanding of the molecular mechanisms that enable tumor cell dissemination is a vital health issue. Epithelialto-mesenchymal transitions (EMTs) endow carcinoma cells with enhanced migratory and survival attributes that facilitate malignant progression. Characterization of EMT effectors is likely to yield new insights into metastasis and novel avenues for treatment. We show that the presence of the receptor tyrosine kinase Axl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
557
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 521 publications
(599 citation statements)
references
References 29 publications
27
557
1
6
Order By: Relevance
“…Here we showed that YW327.6S2 is able to reduce the metastasis of MDA-MB-231 breast cancer cells to the bone. These results are consistent with our previous data that silencing of Axl by RNAi in breast cancer cells inhibits their metastasis to the lung in an orthotropic model (Li et al, 2009;Gjerdrum et al, 2010), suggesting that this anti-Axl antibody could have therapeutic potential not only in the treatment of primary tumor but also in metastatic disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here we showed that YW327.6S2 is able to reduce the metastasis of MDA-MB-231 breast cancer cells to the bone. These results are consistent with our previous data that silencing of Axl by RNAi in breast cancer cells inhibits their metastasis to the lung in an orthotropic model (Li et al, 2009;Gjerdrum et al, 2010), suggesting that this anti-Axl antibody could have therapeutic potential not only in the treatment of primary tumor but also in metastatic disease.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have established the role of Axl in promoting tumor cell migration, invasion and metastasis (Vajkoczy et al, 2006;Tai et al, 2008;Zhang et al, 2008;Li et al, 2009;Gjerdrum et al, 2010). Here we showed that YW327.6S2 is able to reduce the metastasis of MDA-MB-231 breast cancer cells to the bone.…”
Section: Discussionmentioning
confidence: 50%
“…Gas6-activated Axl signaling marshalls important downstream regulators of cell motility such as Rac and Akt (Allen et al, 2002;Hasanbasic et al, 2004) and regulates haptotaxis toward vitronectin in endothelial cells (Holland et al, 2005). Recent studies support a role for Axl as a regulator of glioma, breast, lung and pancreatic tumor cell migration (Shieh et al, 2005;Vajkoczy et al, 2006;Koorstra et al, 2009) and very recently Axl was identified as an important regulator of breast cancer metastasis and survival of patients (Vajkoczy et al, 2006;Gjerdrum et al, 2010). We found that vimentin regulates Axl expression in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 88%
“…The receptor tyrosine kinase AXL is an oncogene shown to promote tumor cell growth, metastasis, and drug resistance to HER2 and epithelial growth factor receptor-targeted therapy. [22][23][24][25] LAMC2 expression has been shown to be associated with prognosis in several solid tumors, 5,9-14 but its role in the metastatic process is not clear.…”
Section: Resultsmentioning
confidence: 99%